BEST PRACTICE COMMUNITY GUYUB COMMUNICATIONIN THE CONSTRUCTION OF THE AL-HIJRAH MOSQUE IN CIMARENG VILLAGE, LEBAK WANGI WALANTAKA DISTRICT, SERANG CITY, BANTEN PROVINCE - Nina Yuliana; Ima Maisaroh, Suja'i (Adisam Publisher, 2024)
The existence of the Al-Hijrah mosque is proof of how the community members amount 120 families, suddenly, unplanned, and with a relatively low level of education and a weak economy, were able to build a mosque at a total cost of around IDR 1.7 billion within six months by relying on local wisdom called Communication Guyub (collaborative, togetherness, mutual cooperation). First, communication uses online and offline media, with offline media being dominant. The main cause is because not all residents have smart phones and internet quota, especially those aged 40 years and over. Second, the area is small and the community system is entrenched, this is the reason why residents prefer to share information directly through daily life activities. This research aims to determine the methods/models of Guyub Communication practices and strategies for residents of the Cimareng neighborhood to produce a mosque worth IDR. 1.7 billion within six months in sudden, unplanned conditions and relatively limited conditions. It is hoped that the findings of this research can inspire and become a variant of other development strategies that improve the welfare of society. The research was conducted using qualitative methods and a situational leadership theory approach